Uso de substâncias psicoativas entre universitários de Psicologia de uma Universidade Pública - Pereira, Denis Soprani (2013)
The use of psychoactive substances is a public health problem, especially among college students, becoming a major focus of research in Brazil. This is worrying, especially in psychology students, since these in their professional life will deal constantly with that issue, and will be models for their students. This study aims to establish the consumption pattern of psychoactive substances by students of Psychology of the Federal University of Espirito Santo (UFES). It was conducted a descriptive, cross-sectional and quantitative study. The sample consisted of 242 students of Psychology UFES, registered in the period 2010. A closed and anonymous questionnaire proposed by the National Drug Policy (SENAD) was used. Statistical analysis was performed using the Statistical Package for the Social Science - SPSS 17, using the univariate analysis, bivariate through the x² test and multivariate analysis by logistic regression. It was found that 79.4% of students are female, 81.3% are aged 18 to 24 years and 40.9% are of Catholic religion. Regarding the use of licit drugs, 85.5% had lifetime use of alcohol and 35.1% had lifetime tobacco use. Among the illicit substances, tranquilizers (20.2%), marijuana (19.8%), inhalants (11.6%) and hallucinogens (7.4%) were the most commonly consumed in life. The factor most strongly associated with illicit drug use was attending the Academic Center (CA), p-value<0.001. Logistic regression showed that this behavior is associated with a 7.378 bigger risk to try illicit drugs. In conclusion, the prevention programs and curricular strategies are necessary to provide the knowledge construction by future psychologists about the topic, from prevention to treatment, based on the biopsychosocial aspects.